2021
DOI: 10.21203/rs.3.rs-524410/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Prognostic Gene Signature Associated with Tumor Microenvironment of Cholangiocarcinoma

Abstract: Background: Cholangiocarcinoma (CCA) is the most common malignancy of the biliary tract with a dismal prognosis. Increasing evidence suggests that tumor microenvironment (TME) is closely associated with cancer prognosis. However, the prognostic signature for CCA based on TME has not yet been reported. This study aimed to develop a TME-related prognostic signature for accurately predicting the prognosis of patients with CCA. Methods: Based on the TCGA database, we calculated the stromal and immune scores using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…Collectively, CHRM3.AS2, MIR205HG, and LINC00661 may regulate autophagy through the above various pathways, leading to differences in survival outcomes according to prognostic characteristics of CCA patients with high-and low-risk scores. Furthermore, similar studies may have been reported, for example, Cao et al (43) reported most recently in May 2021 a similar exploration of DEG signature related to TME for CCA patients' prognosis prediction. Their study emphasized on TME and DEGs, while our study focused on autophagy and DEARlncRNAs, both of which deserve affirmation with positive and promising results generated.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Collectively, CHRM3.AS2, MIR205HG, and LINC00661 may regulate autophagy through the above various pathways, leading to differences in survival outcomes according to prognostic characteristics of CCA patients with high-and low-risk scores. Furthermore, similar studies may have been reported, for example, Cao et al (43) reported most recently in May 2021 a similar exploration of DEG signature related to TME for CCA patients' prognosis prediction. Their study emphasized on TME and DEGs, while our study focused on autophagy and DEARlncRNAs, both of which deserve affirmation with positive and promising results generated.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, similar studies may have been reported, for example, Cao et al. ( 43 ) reported most recently in May 2021 a similar exploration of DEG signature related to TME for CCA patients’ prognosis prediction. Their study emphasized on TME and DEGs, while our study focused on autophagy and DEARlncRNAs, both of which deserve affirmation with positive and promising results generated.…”
Section: Discussionsupporting
confidence: 72%